Central composite design for formulation and optimization of solid lipid nanoparticles to enhance oral bioavailability of Acyclovir - Hassan, Haniza; Adam, Siti Khadijah; Alias, Ekram; Meor Mohd Affandi, Meor Mohd Redzuan; Shamsuddin, Ahmad Fuad; Basir, Rusliza (Multidisciplinary Digital Publishing Institute, 2021)
Treatment of herpes simplex infection requires high and frequent doses of oral acyclovir to attain its maximum therapeutic effect. The current therapeutic regimen of acyclovir is known to cause unwarranted dose-related adverse effects, including acute kidney injury. For this reason, a suitable delivery system for acyclovir was developed to improve the pharmacokinetic limitations and ultimately administer the drug at a lower dose and/or less frequently. In this study, solid lipid nanoparticles were designed to improve the oral bioavailability of acyclovir. The central composite design was applied to investigate the influence of the materials on the physicochemical properties of the solid lipid nanoparticles, and the optimized formulation was further characterized. Solid lipid nanoparticles formulated from Compritol 888 ATO resulted in a particle size of 108.67 ± 1.03 nm with an entrapment efficiency of 91.05 ± 0.75%. The analyses showed that the optimum combination of surfactant and solid lipid produced solid lipid nanoparticles of good quality with controlled release property and was stable at refrigerated and room temperature for at least 3 months. A five-fold increase in oral bioavailability of acyclovir-loaded solid lipid nanoparticles was observed in rats compared to commercial acyclovir suspension. This study has presented promising results that solid lipid nanoparticles could potentially be used as an oral drug delivery vehicle for acyclovir due to their excellent properties.